A New Direction toward Problem-Solving Creativity: Dynamic Capability, Organizational Culture as a Predictor, with Psychological Well-Being as Moderation - Heti Patmawati; Syamsul Hadi; Didik Subiyanto (Faculty of Economics and Business, Universitas Wahid Hasyim, 2024)
Creativity in problem solving is a very important requirement for individuals and organizations to deal with very complex life activities, especially those related to the development of digital technology. Problem solving creativity has emerged as an important concept to support individual success in an institution to solve work problems encountered. The new era of increasing problem-solving creativity is inseparable from the level of dynamic capabilities and the ongoing organizational culture. In addition, individual psychological well-being will be a factor that strengthens or weakens individual activities within the organization. Analyse the influence of dynamic capability and organizational culture on problem solving creativity, and at the same time explore the role of individual psychological well-being in the relationship between dynamic capability and organizational culture on problem solving creativity. This research is a quantitative study involving 150 police personal respondents in East Lampung. The collected data was processed using AMOS software and analysed using Structural Equation Modelling (SEM). It was found empirically, without involving the role of psychological well-being as a moderation, dynamic capability were not proven to influence problem-solving creativity. Meanwhile, by involving psychological well-being, dynamic capability have a positive and significant effect on problem-solving creativity. The next result is that organizational culture is proven to have a significant positive effect on problem solving creativity, both with moderation of psychological well-being and without moderation of psychological well-being. Psychological well-being is proven to strengthen the influence of dynamic capability and organizational culture on problem solving creativity. The results of this study expand knowledge about the factors that influence problem solving creativity, both factors that come from the organization and factors that come from individual psychology. The results of this research will certainly be an important source of input for police institutions, especially in East Lampung, in policies to improve the quality of personnel's problem solving creativity.